2008
DOI: 10.1016/j.brainres.2008.03.084
|View full text |Cite
|
Sign up to set email alerts
|

The decline of cross-species intersensory perception in human infants: Underlying mechanisms and its developmental persistence

Abstract: The current study investigated the mechanisms underlying the developmental decline in cross-species intersensory matching first reported by Lewkowicz and Ghazanfar [Lewkowicz, D.J., & Ghazanfar, A.A., (2006). The decline of cross-species intersensory perception in human infants. Proc. Natl. Acad. Sci. U. S. A. 103(17), 6771-6774] and whether the decline persists into later development. Experiment 1 investigated whether infants can match monkey vocalizations to asynchronously presented faces and found that neit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 50 publications
5
35
0
Order By: Relevance
“…In subsequent studies, we have found that the younger infants perform the cross‐species cross‐modal matches on the basis of audio‐visual synchrony in that when the faces and vocalizations are desynchronized, neither the younger nor older infants match (Lewkowicz, Sowinski, & Place, 2008). In another study, we have found that the broad perceptual tuning is present at birth in that newborns also are able to match corresponding monkey faces and vocalizations and, in addition, can do so even when a tone of the same duration as the audible vocalization is presented instead (Lewkowicz, Leo, & Simion, 2010).…”
Section: Example Of a Process‐oriented Approachmentioning
confidence: 99%
“…In subsequent studies, we have found that the younger infants perform the cross‐species cross‐modal matches on the basis of audio‐visual synchrony in that when the faces and vocalizations are desynchronized, neither the younger nor older infants match (Lewkowicz, Sowinski, & Place, 2008). In another study, we have found that the broad perceptual tuning is present at birth in that newborns also are able to match corresponding monkey faces and vocalizations and, in addition, can do so even when a tone of the same duration as the audible vocalization is presented instead (Lewkowicz, Leo, & Simion, 2010).…”
Section: Example Of a Process‐oriented Approachmentioning
confidence: 99%
“…Although developmental studies have highlighted that significant changes take place in multisensory temporal processing as maturation progresses (Lewkowicz, 1996; Wallace et al, 1997; Wallace and Stein, 1997; Lewkowicz and Ghazanfar, 2006; Lewkowicz et al, 2008), few have looked at the possible malleability of these processes in the adult. Those that have examined the window’s flexibility focused on changes in point measures such as the PSS and have shown that repeated exposure to asynchronous multisensory combinations biases judgments in the direction of the repeated exposure (Fujisaki et al, 2004; Vroomen et al, 2004; Navarra et al, 2005; Vatakis et al, 2007; Hanson et al, 2008; Keetels and Vroomen, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a visual-preference task, 4-month-old infants preferred synchronous over asynchronous presentations of moving stuffed animals with the corresponding impact sounds (Spelke, 1979). Moreover, a number of behavioral studies have demonstrated that, starting from birth (Lewkowicz et al, 2010), human infants rely on audiovisual synchrony for intersensory matching (e.g., Bahrick, 1983; Lewkowicz, 1986, 1992, 2000; Lewkowicz et al, 2008). However, little is known about how the infant neural system creates a synchronous or asynchronous percept.…”
Section: Introductionmentioning
confidence: 99%